Abundance of Phytoplankton in the Peat Soil Media with Given a Mixture of Biofertilizers - Tri Manda R Nababan; Saberina Hasibuan; Syafriadiman Syafriadiman (Jurnal Perikanan dan Kelautan, 2021)
This research was conducted from October to November 2019 at the peatland of Kualu Nenas Village, Kampar District, Riau Province. The aim of this research is to get a comparison of the mixture between human waste biofertilizer and cow manure biofertilizer to increased the abundance of phytoplankton. The method used in this study is an experimental method using a completely randomized design (CRD), 1 factor with 6 treatment levels and 3 replications. The treatment used were P0 (without biological fertilizers), P1 (giving a mixture of biological fertilizer 100%), P2 (Biofertilizer mixture 25% human waste : 75% cow manure biofertilizer), P3 (Biofertilizer mixture 50% human waste : 50% cow manure biofertilizer), P4 (Biofertilizer mixture 75% human waste: 25% cow manure biofertilizer), P5 (Biofertilizer 100% human waste). The study was conducted for 28 days, using a dose of 750 g/m2. The results of this research showed that the application of a mixture of biological fertilizers 75% human waste: 25% biofertilizer cow manure gave the best results on the abundance of phytoplankton, namely 28,771 ind/L, the diversity index value (H') was 0.49, the species dominance value (C) was 1.10 and the peak of the population occurred on the 16th day. Water quality parameters measured during the study were still optimal for phytoplankton growth with a temperature of 27-29oC, pH 5-7, DO 3.8-6.7 ppm, nitrate 4.75 mg/L, and orthophosphate 3.50 mg/L.